Role of Circulating Tumor DNA in Gastrointestinal Cancers: Update From Abstracts and Sessions at ASCO 2018 - Shahjehan, Faisal; Kamatham, Saivaishnavi; Kasi, Pashtoon Murtaza (Frontiers in Oncology, 2019)
Background: The promising aspect of circulating tumor DNA (ctDNA) is its rapid turnaround and non-invasive nature. According to the American Society of Clinical Oncology (ASCO) and College of American Pathologists joint ctDNA review published in March 2018, there is not sufficient evidence to support the use of ctDNA in practice for GI cancers. However, there were numerous studies presented at ASCO Annual Meeting supporting its value. We aimed to summarize on its role in the management of gastrointestinal cancers based on the studies presented recently, and future directions. Methods: We limited our search to keywords “ctDNA,” “circulating tumor DNA,” “cell-free DNA (cfDNA)” and/or “liquid biopsy,” at the 2018 ASCO Annual Meeting library abstracts and presentations. Results: There were 35 studies that revolved around ctDNA as a diagnostic tool, prognostic marker and/or a measure of tumor heterogeneity in gastrointestinal cancers. Depending on the assay used, the results of several studies showed that ctDNA was able to identify relevant mutations or fusions including RAS, HER2/Neu, BRAF, MET, BRCA2, APC, TP53, ALK, ROS1, PTEN, and NF1. The prognosis in terms of tumor mutation burden, objective response rate, metastasis and survival were also estimated by various studies based on ctDNA. The findings showed that higher baseline ctDNA levels and/or increased number of mutations detected in ctDNA were associated with poor survival and multi-site metastasis. Right-sided colon cancer was associated with higher number of mutations in ctDNA than left-sided colon and rectal cancers. Similarly, tubular adenocarcinoma subtype of gastric cancer was more likely to have higher ctDNA levels than signet-ring cell subtype. The feasibility of assessing response to therapy and residual metastatic disease by using ctDNA which was otherwise not detected on imaging was also presented. Conclusions: The studies presented at ASCO 2018 report on the many ways ctDNA is of value in patients with gastrointestinal malignancies. Experts and discussants at the meeting argued that this may well indeed be ready for prime time for certain GI malignancies including colorectal cancers, especially in the metastatic setting. These findings alongside ongoing studies showing its feasibility into practice would likely lead to revision of the current guidelines for metastatic GI cancers.